(untitled) (Nexo Revista Científica, 2023)
A collaborative model and an eco-friendly module have been implemented in order to allow the fair commercialization of the fiber and good management of alpaquero herds. For the construction and progress of this proposal, a collaborative model development process was designed, made up of two units: the identification of community members, for the search for Andean communities and selection of community members; and the execution of the model, for the service of upbringing and return of guarantees. Also, a process was designed for the eco-friendly module consisting of three units: the acquisition of raw material for the reception/breeding of alpacas and fleece shearing; the production of fiber and yarn and the sale of fiber-based products. Data was taken from 22 alpacas in order to obtain a record of their progress with the care provided to them in the module; The results show the improvement of 90% of alpacas that initially had some discomfort, the increase in the quality of fiber in 60% of the alpacas, the identification and controlled mating of the alpacas not served, the reduction of intermediaries in the commercialization of fiber and the improvement in the income received by the breeder.